Assessment of the oral health knowledge of healthcare providers in geriatric nursing homes: additional training needs required. (8th December 2013) - Catteau, Céline; Piaton, Sophie; Nicolas, Emmanuel; Hennequin, Martine; Lassauzay, Claire
Abstract : Objectives: This study was aimed at assessing the knowledge of oral health and training needs of health workers in geriatric nursing homes. Background: Providing daily oral care to dependent elderly people is the best way to prevent oral disorders. Because there are no dental hygienists in France, health workers play an important role in providing oral care in nursing homes and should have correct and adequate knowledge. Materials and methods: Health workers from 8 geriatric nursing homes in Puy de Dôme (France) completed a 58‐item questionnaire. Oral health knowledge regarding dental decay, periodontal diseases, oral hygiene and denture care was assessed. Univariate and bivariate analyses were performed. Results: A total of 99 health workers took part in the study. The total mean score was significantly different if health workers had received training in oral disorders (49.3 ± 11.7 vs. 43.9 ± 10; p  < 0.05) or in the maintenance of oral health (50.5 ± 10.5 vs. 42.9 ± 10; p  < 0.01). The mean scores obtained in the 'dental decay' subsection and in the 'oral and denture hygiene' subsection were the lowest. Conclusion: Geriatric nursing home staff need training in understanding the impact of oral health on general health. Theoretical knowledge of oral diseases has to be improved in order for health workers to understand oral hygiene procedures and to help them identify early oral disorders.